The Man Who Knew Infinity: Main Character’s Speech Acts Revealed His Cultural Identity - Nabila Febrizia Putri; Lina Purwaning Hartanti (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. The purposes of this study are (1) to classify speech acts’ types and functions performed by the main character; and (2) to discover how those speech acts’ functions reveal the main character’s cultural identityThis study is aimed to reveal the speaker’s cultural identity through his utterances by recognizing their speech acts functions. The qualitative method is used in this study by applying documentation technique as the data collection and the researcher as the instrument of the study. Data of this study were taken from two selected scenes. The analysis technique was conducted through three steps; data condensation, data display, and conclusion drawing and verification. The data are presented in a table and descriptive after the utterances were transcribed. This study’s results can be concluded as follows (1) 15 speech act utterances are belong to illocutionary act followed by the largest portion of 7 representative functions, 4 expressive functions, 2 directive functions, and 2 declaration functions and (2) 6 out of 7 cultural identity aspects were revealed through those speech act functions performances; cultural narrative, identity centrality, identity salience, cultural roles and roles enactments, and cultural regard. Regarding the results, it can be implied that within genuine conversations there’s a tendency that someone’s utterances mostly carrying representative functions. Keywords: Main Character, Cultural Identity